2010
DOI: 10.1055/s-0030-1268854
|View full text |Cite
|
Sign up to set email alerts
|

2-Octylcyanoacrylate-Assisted Microvascular Anastomosis in Rat Orthotopic Small Bowel Transplantation

Abstract: The purpose of this study was to investigate the potential advantages of 2-octylcyanoacrylate-assisted end-to-side arterial anastomosis over continuous suture-only anastomosis in the rat orthotopic small bowel transplantation (OSBT) model. OSBT was performed in 80 Sprague-Dawley rats, and they were divided into two groups. Group 1 was the study group (n = 40), using 2-octylcyanoacrylate-assisted end-to-side arterial anastomosis. Group 2 was the control group (n = 40), using a running 9-0 prolene suture only. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…21 However, more experimental research would be advised to be conducted in order to clarify the terms and have suitable guidelines as to when the technique can be safely indicated. 15,27 Given the fact that recent studies have shown less perivascular inflammatory tissue together with neointimal hyperplasia when comparing chemical synthetic adhesives to sutures only technique, raising the possibility that the reduced exposure to chronic inflammatory mediators may result in better long-term anastomotic patency rates by reduction in fibrogenesis and scarring, make it even more likely that with further research the aforementioned technique would be suitable for clinical practice. 15 The clinical use of chemical synthetic adhesives in vascular anastomosis, either used as adjuvants or as a stand-alone technique, could bring better overall results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 However, more experimental research would be advised to be conducted in order to clarify the terms and have suitable guidelines as to when the technique can be safely indicated. 15,27 Given the fact that recent studies have shown less perivascular inflammatory tissue together with neointimal hyperplasia when comparing chemical synthetic adhesives to sutures only technique, raising the possibility that the reduced exposure to chronic inflammatory mediators may result in better long-term anastomotic patency rates by reduction in fibrogenesis and scarring, make it even more likely that with further research the aforementioned technique would be suitable for clinical practice. 15 The clinical use of chemical synthetic adhesives in vascular anastomosis, either used as adjuvants or as a stand-alone technique, could bring better overall results.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect is crucial in microvascular surgery as to avoid undesirable complications. 11,13,15,23,[25][26][27] Moreover, this could be of great addition for trainees with little experience since it does not require substantial training as the gold standard technique does; however, this does not imply that adequate training should not be acquired throughout one's surgical curriculum. 1 Secondly, the use of chemical synthetic adhesives is thought to be highly thrombotic once they would leak inside the vessel whenever compared to the classic technique, compromising the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24] Furthermore, 2-OCA is a long-chain molecule that has fewer side effects and is less toxic than short-chain cyanoacrylates. 1,21,25,26 The dose of the adhesive should be minimized to reduce the risk of adhesive leakage into the lumen. 22 The minimal use of cyanoacrylate will also reduce the histotoxic effects on vessels.…”
Section: Discussionmentioning
confidence: 99%